Pola efikasi guru-guru novis sekolah menengah - Johari, Khalid (UUM College of Arts and Sciences, 2009)
Purpose – This study was aimed at determining the level of teacher efficacy among novice teachers in 21 secondary schools in Sabah, Malaysia. It also intended to investigate if there is any difference in teacher efficacy with respect to gender, types of teacher training and teaching subject. Method – Using the causal comparison design study, data were collected using the Teacher Sense of Effi cacy Scale from 176 novice teachers. Findings – The mean obtained for teacher efficacy was moderately high, with novice teachers being more efficacious in class management. The findings showed that there were significant differences in teacher efficacy according to gender, types of teacher training, and teaching subject. The types of teacher training was found to be the main contributor to the variance in teacher efficacy as compared to gender and teaching subject. Value – The study might implicate the conventional practice in school systems pertaining to professionalism opportunities upon novice teachers.